Digital soil map of the world - Sánchez, P.A.; Ahamed, S; Carre, F; Hartemink, A.E.; Hempel, J; Huising, Jeroen; Lagacherie, Philippe; McBratney, AB; McKenzie, N; Mendonça Santos, M.L.; Minasny, B; Montanarella, Luca; et al. (American Association for the Advancement of Science, 2009)
Soils are increasingly recognized as major contributors to ecosystem services such as food production and climate regulation (1, 2), and demand for up-to-date and relevant soil information is soaring. But communicating such information among diverse audiences remains challenging because of inconsistent use of technical jargon, and outdated, imprecise methods. Also, spatial resolutions of soil maps for most parts of the world are too low to help with practical land management. While other earth sciences (e.g., climatology, geology) have become more quantitative and have taken advantage of the digital revolution, conventional soil mapping delineates space mostly according to qualitative criteria and renders maps using a series of polygons, which limits resolution. These maps do not adequately express the complexity of soils across a landscape in an easily understandable way.